Toying with arthropods. - Tan, Ming Zhi. (2012)
Through the eyes of a child, an insect crouching on the wall conjures up mixed feelings in them. Disgust, fear, paranoia, intrigue, inquisitiveness, wonder or even playful feelings are stirred. As adults and children grow up, they become immune and indifferent to the design of nature.